Method for preparing regenerated bis(2-hydroxyethyl) terephthalate by multi-step depolymerization
Patent Information
- Application Number
- JP2024544839
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-21
- Publication Date
- 2025-03-13
Smart Images

Figure 2025506628000001_ABST
Abstract
Description
Detailed Description of the Invention
[0001] [Technical field] The present invention relates to a method for preparing high-purity, high-quality recycled bis(2-hydroxyethyl) terephthalate (BHET) using waste polyester.
[0002] [Background technology] Among the polymers commonly used in modern life, polyester is widely used as a material for beverage containers, packaging films, audio and video films, etc., due to its excellent mechanical strength, heat resistance, transparency, and gas barrier properties. In addition, polyester is widely produced around the world as an industrial material for medical fibers, tire cords, etc. In particular, polyester sheets or polyester plates have good transparency and excellent mechanical strength, and are therefore widely used as raw materials for cases, boxes, partitions, shelves, panels, packaging materials, building materials, interior and exterior materials, etc.
[0003] As a result, plastic waste such as polyester is generated at an uncontrollable level worldwide every year. In recent years, various countries around the world have formulated regulations and plans for the recycling of waste plastic resources, including waste polyester. Physical and chemical methods are used to recycle waste polyester, but physical recycling methods cannot guarantee purity and are not widely used.
[0004] In chemical recycling, the ester bonds of waste polyester are broken to depolymerize it. Reactions such as glycolysis, hydrolysis, methanolysis, and aminolysis are used. Among these, glycolysis is the decomposition of waste polyester by adding glycols such as ethylene glycol or diethylene glycol at high temperature. The reaction product obtained mainly contains bis(2-hydroxyethyl) terephthalate (BHET).
[0005] After crystallization or purification, bis(2-hydroxyethyl) terephthalate can be used as a raw material for preparing unsaturated polyester or ester polyols.
[0006] [Prior art document] [Patent Document 1] Korean Patent No. 1386683 [Patent Document 2] U.S. Patent No. 7,211,193 [Non-Patent Document 1] Park, SH., Kim, SH., Poly(ethylene terephthalate) recycling for high value added textiles, Fashion and Textiles 1, 1 (2014)
[0007] [Disclosure of the Invention] [Technical issues] In general, the products of the depolymerization reaction of waste polyester resin contain large amounts of oligomers such as dimers and trimers in addition to bis(2-hydroxyethyl) terephthalate (BHET). Since diethylene glycol (DEG) is formed at high depolymerization temperatures, the formation of by-products derived from diethylene glycol is inevitable.
[0008] For example, diethylene glycol esters (DEG esters) cause degradation of physical properties during polymerization of recycled polyester resins, and even more so for polyester copolymers, and furthermore, the color of the polymerization raw material becomes dark and yellow, which inevitably limits the use of this raw material.
[0009] In order to solve this problem, the inventors have conducted research and discovered that it is possible to produce BHET in high purity by carrying out the depolymerization reaction in multiple stages, with the temperature in the latter stages being significantly reduced, thereby reducing the formation of diethylene glycol and impurities derived from diethylene glycol.
[0010] Furthermore, we were able to prepare BHET with improved color quality by further performing ion exchange and distillation of unreacted glycols after the depolymerization reaction, thereby reducing the formation of oligomers and removing the chromophores.
[0011] Therefore, the object of the present invention is to provide a method for preparing high-purity and high-quality regenerated bis(2-hydroxyethyl) terephthalate (BHET) using waste polyester through a multi-step depolymerization reaction together with separation and purification steps.
[0012] [Means to solve the problem] The present invention provides a method for preparing recycled bis(2-hydroxyethyl) terephthalate, comprising the steps of: (1) subjecting waste polyester to depolymerization by a first glycolysis reaction at a temperature of 180°C to 200°C to obtain a first reactant; (2) subjecting the first reactant to depolymerization by a second glycolysis reaction at a temperature of 150°C to 170°C to obtain a second reactant; (3) subjecting the second reactant to ion exchange by an ion exchange resin to obtain a third reactant; (4) removing unreacted glycol from the third reactant by distillation at a temperature of 150°C or less to obtain a fourth reactant; and (5) subjecting the fourth reactant to distillation to obtain crude bis(2-hydroxyethyl) terephthalate.
[0013] Furthermore, the present invention provides a regenerated bis(2-hydroxyethyl) terephthalate prepared by the above method, which has a total peak area fraction of bis(2-hydroxyethyl) terephthalate of 96% or more and a peak area fraction of diethylene glycol ester compounds of less than 2% when measured by high performance liquid chromatography (HPLC).
[0014] [Advantageous Effects of the Invention] According to the method of the present invention, the depolymerization reaction is carried out in multiple stages with a significantly reduced temperature in the latter stages, thereby reducing the formation of diethylene glycol and impurities derived from diethylene glycol, thereby producing recycled bis(2-hydroxyethyl)terephthalate (BHET) with high purity. Furthermore, according to the method of the present invention, bis(2-hydroxyethyl)terephthalate (BHET) with improved quality in terms of color can be prepared by further carrying out ion exchange and distillation of unreacted glycol after the depolymerization reaction, thereby reducing the formation of oligomers and removing chromophores.
[0015] Therefore, the present invention not only makes it possible to recycle resources by depolymerizing waste polyester, but also makes it possible to produce high-quality polyester resins and products using the recycled bis(2-hydroxyethyl) terephthalate produced by the present invention as a raw material. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 illustrates a method for preparing regenerated bis(2-hydroxyethyl) terephthalate according to one embodiment.
[0017] [Best Mode for Carrying Out the Invention] Various embodiments and examples will be described in detail below with reference to the drawings.
[0018] In this specification, the terms used to refer to the various components are used to distinguish them from one another and are not intended to limit the scope of the embodiments. Furthermore, in this specification, the singular expressions are to be construed as including the plural as well, unless otherwise indicated by the context.
[0019] In this specification, terms such as first, second, etc. are used to describe various components. However, the components should not be limited by the terms. The terms are used only to distinguish one element from another element.
[0020] As used herein, the term "comprising" is intended to specify certain features, regions, steps, methods, elements, and / or components, and does not exclude the presence or addition of any other features, regions, steps, methods, elements, and / or components, unless specifically stated to the contrary.
[0021] The method for preparing recycled bis(2-hydroxyethyl) terephthalate according to the present invention includes the steps of: (1) subjecting waste polyester to depolymerization by a first glycolysis reaction at a temperature of 180°C to 200°C to obtain a first reactant; (2) subjecting the first reactant to depolymerization by a second glycolysis reaction at a temperature of 150°C to 170°C to obtain a second reactant; (3) subjecting the second reactant to ion exchange by an ion exchange resin to obtain a third reactant; (4) removing unreacted glycol from the third reactant by distillation at a temperature of 150°C or less to obtain a fourth reactant; and (5) subjecting the fourth reactant to distillation to obtain crude bis(2-hydroxyethyl) terephthalate.
[0022] Before step (1), a step of crushing the waste polyester to a size below a certain level may be further carried out. Furthermore, a step of cooling the second reaction product obtained in step (2) to a temperature below a certain level may be further carried out. Furthermore, before step (3), a step of removing insoluble impurities from the second reaction product by filtration may be further carried out. Furthermore, after the distillation in step (5), a step of adsorbing and crystallizing the crude bis(2-hydroxyethyl) terephthalate may be further carried out.
[0023] FIG. 1 shows a method for preparing recycled bis(2-hydroxyethyl) terephthalate according to one embodiment. Referring to FIG. 1, first, waste polyester is crushed to a size of 4 mm or less (S100), ethylene glycol is added thereto, and then the mixture is subjected to a first glycolysis reaction at a temperature of 180°C to 200°C in the presence of zinc acetate catalyst for about 2 hours (S210), and ethylene glycol is further added thereto, and then the mixture is subjected to a second glycolysis reaction at a temperature of 150°C to 170°C for about 2 hours (S220). After that, the mixture is cooled to 120°C or less using a vacuum flash (S300), a small amount of filter aid is added thereto, and then insoluble impurities are filtered and separated by solid-liquid separation (S400), and ion exchange is performed by passing through a column filled with ion exchange resin (S500). Next, unreacted glycol is recovered at a temperature of 100°C to 130°C (S600), purification is performed by thin-film distillation at 190°C to 250°C (S700), and finally an adsorption-crystallization step (S800) is performed to obtain high-purity, high-quality bis(2-hydroxyethyl) terephthalate.
[0024] Each step will now be described in detail.
[0025] (Preparation of waste polyester) The waste polyester used as the raw material in the present invention can be obtained from polyester material products that have been discarded after use.
[0026] For example, waste polyester can be obtained from products such as beverage bottles, fabrics, films, cases, boxes, dividers, shelves, protective panels, packaging materials, building materials, and interior and exterior materials made from various polyester materials that are discarded after use by consumers.
[0027] The waste polyester material may be pre-treated before being subjected to the depolymerization step.
[0028] First, the waste polyester material is cleaned of other plastics, metals, and contaminants, and then washed and sorted, if necessary, according to specific characteristics such as color.
[0029] The waste polyester material thus selected is put into a crusher and crushed into small flakes. The waste polyester flakes thus obtained may be sieved into a desired particle size or less using a mesh. The size of the mesh may be, for example, 4 mm or less, 3 mm or less, or 2 mm or less.
[0030] The sieved flakes can be washed, dried, such as with hot air, and then subjected to a depolymerization step.
[0031] On the other hand, the waste polyester subjected to the glycolysis reaction may have a controlled particle size. For example, the waste polyester may be pulverized into flakes by the above-mentioned pretreatment step.
[0032] Specifically, the particle size of the waste polyester may be 4 mm or less, 3 mm or less, 2 mm or less, or 1 mm or less. If the particle size is within the above range, the glycolysis reaction can be performed under relatively low temperature conditions. For example, the temperature condition of the first glycolysis reaction may be adjusted to 195°C or less, 190°C or less, 185°C or less, or 180°C, and the temperature condition of the subsequent second glycolysis reaction may be adjusted to 160°C or less or 150°C or less. Furthermore, if the particle size is within the above range, the glycolysis reaction can be performed within a relatively short time. For example, the time of the first and second glycolysis reactions may be 3 hours or less, 2 hours or less, or 1 hour or less from the time when the appropriate temperature is reached.
[0033] Furthermore, the waste polyester may have a fine structure like a fiber. For example, the waste polyester may be waste fiber or fibrous material such as a discarded banner.
[0034] As a specific example, the waste polyester may have a particulate or fibrous form with a particle size of 4 mm or less.
[0035] The fibers may include at least one of monofilament yarns and multifilament yarns. The diameter of the monofilament yarn may be, for example, 0.05 denier to 100 denier, which may correspond to about 0.001 mm to 0.1 mm. Specifically, the monofilament yarn may have a diameter of 0.05 denier to 7 denier, or 7 denier to 100 denier. The diameter of the multifilament yarn may be, for example, 1 denier to 10,000 denier, which may correspond to about 0.01 mm to 1 mm. Specifically, the multifilament yarn may have a diameter of 0.01 denier to 0.2 denier, or 0.2 denier to 1 denier.
[0036] When the particle size or diameter of the waste polyester is adjusted to fall within a specific range and depolymerization is carried out, solvation can be promoted even under conditions of a relatively low temperature and a short reaction time.
[0037] In particular, according to the subject invention, a two-stage glycolysis reaction (i.e., a first glycolysis reaction and a second glycolysis reaction) is carried out. When solvation is promoted in the first glycolysis reaction, the second glycolysis reaction can carry out the transesterification reaction of the waste polyester under conditions of a lower temperature and a shorter reaction time. Therefore, the concentration of diethylene glycol (DEG) naturally formed at a general glycolysis reaction temperature can be significantly reduced, and the content of diethylene glycol ester compounds (DEG esters) in the finally prepared recycled bis(2-hydroxyethyl) terephthalate can be significantly reduced.
[0038] The diethylene glycol ester compounds present in the recycled bis(2-hydroxyethyl) terephthalate act as a factor in disrupting the order of the final polymer during the subsequent polymerization of polyesters and polyester copolymers, thereby degrading the heat resistance properties of the final polymer, such as melting point (Tm), glass transition temperature (Tg), etc.
[0039] However, polyester resins and products made using regenerated bis(2-hydroxyethyl) terephthalate obtained by the depolymerization method of the present invention can be polymerized into polymers that do not have unwanted structural defects, as occurs when virgin, non-recycled raw materials are used.
[0040] (Depolymerization) According to the method of the present invention, waste polyester is subjected to pretreatment by pulverization and to a multi-stage depolymerization reaction at a low temperature, so that the content of glycol dimer (diethylene glycol) formed during the depolymerization reaction can be significantly reduced, which has the advantages of improving the purity of the finally obtained regenerated bis(2-hydroxyethyl) terephthalate and minimizing the side reaction structure in the subsequent repolymerization into polyester.
[0041] According to one embodiment, the depolymerization comprises subjecting the waste polyester to depolymerization via a first glycolysis reaction at high temperature (180-200°C) to obtain a first reactant, and subjecting the first reactant to depolymerization via a second glycolysis reaction at low temperature (150-170°C) to obtain a second reactant.
[0042] As is well known, glycolysis refers to a chemical reaction in which a polymer chain or the like is broken down by glycol. The glycol may include, for example, at least one selected from the group consisting of ethylene glycol, propylene glycol, and diethylene glycol.
[0043] A catalyst may be used for the glycolysis reaction. The catalyst may be a metal catalyst, such as a metal salt catalyst or a metal organic catalyst. Specifically, the catalyst may be a metal acetate, carbonate, oxide, or hydroxide, and the metal may be an alkali metal, an alkaline earth metal, or a transition metal.
[0044] Specific examples of the catalyst include metal acetates or their anhydrides or hydrides, and more specifically, may be at least one selected from the group consisting of zinc acetate, sodium acetate, cobalt acetate, manganese acetate, or their hydrates or anhydrides.
[0045] The total weight of the glycol to be added may be 1, 2, or 3 times or more, and may be 7, 5, or 4 times or less, of the weight of the waste polyester resin. For example, the weight of the glycol to be added may be 1 to 7 times, specifically 2 to 5 times, and more specifically 3 to 4 times, the weight of the waste polyester resin.
[0046] Furthermore, the weight of the catalyst to be added may be 0.01 parts by weight or more, 0.1 parts by weight or more, 0.2 parts by weight or more, or 0.3 parts by weight or more, and may be 5 parts by weight or less, 1 part by weight or less, 0.7 parts by weight or less, 0.5 parts by weight or less, or 0.4 parts by weight or less, relative to 100 parts by weight of the waste polyester resin. For example, the weight of the catalyst to be added may be 0.1 parts by weight to 1 part by weight, specifically 0.2 parts by weight to 0.7 parts by weight, relative to 100 parts by weight of the waste polyester resin. More specifically, the catalyst may be used in an amount of 0.2 parts by weight to 0.4 parts by weight relative to 100 parts by weight of the waste polyester.
[0047] The temperature during the first glycolytic reaction may be 170° C. or more, 180° C. or more, or 190° C. or more, and may be 205° C. or less, 200° C. or less, 195° C. or less, or 190° C. or less. For example, the temperature during the first glycolytic reaction may be 180° C. to 200° C., specifically 180° C. to 195° C., and more specifically 180° C. to 190° C.
[0048] Furthermore, the temperature during the second glycolytic reaction may be 140° C. or higher, 150° C. or higher, or 160° C. or higher, and may be 170° C. or lower, or may be 160° C. or lower. For example, the temperature during the second glycolytic reaction may be 150° C. to 170° C., specifically 150° C. to 160° C., and more specifically 150° C. to 155° C.
[0049] The time required for the first and second glycolytic reactions may be 1 hour or more, or 2 hours or more, or 4 hours or less, or 3 hours or less, from the time when the appropriate temperature is reached. For example, the time required for the first and second glycolytic reactions may be 1 hour to 4 hours, specifically 1 hour to 3 hours, and more specifically 1 hour to 2 hours, from the time when the appropriate temperature is reached.
[0050] As a specific example, the first glycolytic reaction may be carried out for 1 to 3 hours at a temperature of 180° C. to 190° C. Furthermore, the second glycolytic reaction may be carried out for 1 to 3 hours at a temperature of 150° C. to 160° C.
[0051] As an example, the first glycolysis reaction may be carried out in the presence of anhydrous zinc acetate catalyst. As a specific example, the first glycolysis reaction may be carried out in the presence of anhydrous zinc acetate catalyst at a temperature of 180°C to 200°C for 1 hour to 3 hours. The anhydrous zinc acetate catalyst may be used in an amount of 0.2 parts by weight to 0.4 parts by weight per 100 parts by weight of waste polyester. Furthermore, the second glycolysis reaction may be carried out at a temperature of 140°C to 160°C for 1 hour to 3 hours without adding a catalyst and by further adding ethylene glycol.
[0052] (cooling and filtering) The second reactant obtained by depolymerization can then be cooled and used in the next step.
[0053] The cooling temperature may be, for example, 150°C or less, 140°C or less, 130°C or less, 120°C or less, 110°C or less, or 100°C or less, or may be 50°C or more, 60°C or more, 70°C or more, 80°C or more, or 90°C or more.
[0054] As an example, cooling may be accomplished by a reduced pressure flash process, in which a vacuum is applied to evaporate ethylene glycol, thereby reducing the temperature of the second reactant.
[0055] For example, the second reactant may be further subjected to a step of cooling to below 120° C. by a vacuum flash prior to the subsequent step. More specifically, the temperature of the second reactant may be reduced to below 110° C. or below 100° C. by a vacuum flash process.
[0056] The pressure condition of the reduced pressure flash process may be, for example, 200 Torr or less, 100 Torr or less, or 50 Torr or less, specifically, 10 Torr to 200 Torr, 10 Torr to 100 Torr, or 10 Torr to 50 Torr.
[0057] Thereafter, insoluble impurities can be removed from the cooled second reactant by filtration. As a specific example, before the ion exchange in step (3), a step of cooling the second reactant to 120°C or less, adding a filter aid, and filtering the second reactant may be further performed. As a result, fine particles and insoluble organic matter present in the second reactant can be filtered and removed by solid-liquid separation.
[0058] Known components such as diatomaceous earth, perlite, and asbestos powder can be used as a filter aid. For example, 0.1 to 2.0 parts by weight of the filter aid may be added to 100 parts by weight of the second reactant.
[0059] Since the bis(2-hydroxyethyl) terephthalate (BHET) or oligomer obtained by the depolymerization reaction exists in a solid state at room temperature, it is difficult to separate the impurities at room temperature. Therefore, it is preferable to separate the impurities at a temperature condition of 90°C to 150°C, more specifically, 110°C to 150°C. Furthermore, when the above temperature range is maintained, the fluidity is good, so that insoluble impurities may be easily removed.
[0060] Various methods and devices can be used to remove insoluble impurities by solid-liquid separation. For example, devices such as a pressure filter, a centrifuge, a filter press, a belt press, etc. may be used. However, as long as any method capable of separating impurities is used, it is not limited thereto.
[0061] (Ion exchange) The depolymerized, cooled and filtered second reactant is subjected to ion exchange with an ion exchange resin to obtain a third reactant.
[0062] When the second reactant is subjected to ion exchange, ionic impurities present in the second reactant, in particular catalysts and contaminants, can be removed.
[0063] As is well known, an ion exchange resin refers to a resin or polymer that functions as a medium for ion exchange, and can include cation exchange resins, anion exchange resins, amphoteric ion exchange resins, chelating resins, and the like.
[0064] The cation exchange resin may include a strongly acidic cation exchange resin having a sulfonic acid group (-SO3H) and a weakly acidic cation exchange resin having a carboxyl group (-COOH).The anion exchange resin may include a strongly basic anion exchange resin in the form of a quaternary ammonium salt and a weakly basic anion exchange resin having a primary to tertiary amino group.
[0065] As a specific example, the ion exchange resin may include at least one selected from the group consisting of a strong acid cation exchange resin, a weak acid cation exchange resin, and a chelating resin.
[0066] According to one embodiment, the ion exchange is carried out by adding an ion exchange resin to the second reactant.
[0067] The weight of the ion exchange resin added may be 1, 3, or 5 times or more, or may be 20, 15, 10, or 8 times or less, of the weight of the catalyst added in the depolymerization reaction. For example, the weight of the ion exchange resin added may be 1 to 20 times, specifically 3 to 15 times, and more specifically 5 to 8 times, the weight of the catalyst added in the depolymerization reaction.
[0068] Furthermore, the weight of the ion exchange resin to be added may be 1 part by weight or more, 3 parts by weight or more, or 5 parts by weight or more, and may be 50 parts by weight or less, 20 parts by weight or less, 15 parts by weight or less, 10 parts by weight or less, or 7 parts by weight or less, based on 100 parts by weight of the waste polyester resin used in the depolymerization reaction.
[0069] As a specific example, the ion exchange resin may be used in an amount of 1 part by weight to 20 parts by weight based on 100 parts by weight of the waste polyester.
[0070] According to another embodiment, the ion exchange is carried out using a column containing an ion exchange resin.
[0071] Specifically, a column can be packed with particles of ion exchange resin, and ion exchange can occur while the second reactant is passed through the column.
[0072] The particle size of the ion exchange resin particles may be, for example, 0.3 mm to 1.5 mm, and more specifically, 0.6 mm to 0.9 mm.
[0073] The ion exchange temperature may be, for example, 140°C or less, 130°C or less, 120°C or less, 110°C or less, or 100°C or less, or 50°C or more, 60°C or more, 70°C or more, 80°C or more, or 90°C or more.
[0074] (Removal of unreacted glycol) Unreacted glycol is removed from the third reactant by distillation to obtain a fourth reactant.
[0075] Since unreacted glycol remains in the depolymerization product after its filtration in the previous step, it is necessary to remove the unreacted glycol from the reaction product prior to the next step.
[0076] Furthermore, in order to make the depolymerization process economical, it is necessary to carry out a step of recovering the unreacted glycols, i.e., the glycols previously used in the depolymerization and remaining without participating in the glycolysis reaction, such as ethylene glycol, propylene glycol, diethylene glycol, etc., can be recovered and reused.
[0077] The distillation to remove the unreacted glycol can be carried out, for example, by vacuum distillation. For this purpose, a glass distillation apparatus or a rotary evaporator may be used.
[0078] The vacuum distillation for removing the unreacted glycol is carried out at a temperature of 150°C or less, which further reduces the formation of diethylene glycol and impurities derived from diethylene glycol, thereby increasing the purity of BHET. For example, the vacuum distillation for removing the unreacted glycol may be carried out at a temperature of 150°C or less, 130°C or less, or 120°C or less, and 80°C or more, 90°C or more, 100°C or more, or 110°C or more. Specifically, the temperature during the distillation for removing the unreacted glycol may be 80°C to 190°C, or 90°C to 150°C. As a more specific example, the distillation for removing the unreacted glycol may be carried out at a temperature of 100°C to 130°C.
[0079] The pressure during distillation to remove unreacted glycol may be, for example, from 0.1 Torr to 200 Torr, more specifically, from 0.5 Torr to 30 Torr.
[0080] (distillation) The fourth reaction product from which the unreacted glycol has been removed is subjected to distillation to obtain crude bis(2-hydroxyethyl) terephthalate.
[0081] Although a variety of methods may be used for distillation, a distillation method that separates the mixture into a thin film to increase the surface area in contact with the heat source can be used.
[0082] For example, the distillation can be carried out by thin film evaporation, falling film evaporation, or short path evaporation. For this purpose, thin film evaporators, falling film evaporators, and short path evaporators, respectively, can be used.
[0083] As a specific example, the distillation for obtaining bis(2-hydroxyethyl) terephthalate may be performed by thin-film evaporation. Specifically, the mixture supplied to the evaporator of the thin-film evaporator forms a thin film on the inner wall of the thin-film evaporator by the wiper rotor. Then, the distillation is performed under appropriate temperature conditions by heating. Furthermore, a cooler for recovering the evaporant may be provided inside the thin-film evaporator.
[0084] Thin film evaporation may be performed by short path evaporation. Such short path and thin film evaporation has a short residence time and allows reduced pressure distillation under high vacuum, making it possible to separate high boiling point or high molecular weight substances that are difficult to separate by other distillation methods while minimizing changes in reactants due to heat. Furthermore, when the pressure inside the thin film evaporator is reduced, the vapor pressure of the substance is lowered, which has the advantage that evaporation can be performed at a temperature lower than the original boiling point.
[0085] In a specific example, the fourth reactant is fed into a short-path and thin-film evaporator, and the wiper for forming the thin film is rotated at 300 rpm or more, so that the evaporated and non-evaporated materials can be separated from each other.
[0086] The internal thin film temperature at the upper part of the thin film evaporator during thin film evaporation may be, for example, 100°C or more, 110°C or more, 120°C or more, or 125°C or more, and may be 250°C or less, 200°C or less, 150°C or less, or 135°C or less, specifically, 150°C to 250°C, 190°C to 250°C, or 180°C to 220°C.
[0087] Furthermore, the internal pressure of the upper part of the thin film evaporator during the thin film evaporation may be, for example, 0.005 Torr to 5.0 Torr, specifically, 0.05 Torr to 5.0 Torr, 0.05 Torr to 1.5 Torr, or 0.05 Torr to 1 Torr. More specifically, the distillation for obtaining crude bis(2-hydroxyethyl) terephthalate may be performed by thin film evaporation under a pressure of 0.05 Torr to 0.4 Torr.
[0088] (adsorption-crystallization) The crude bis(2-hydroxyethyl) terephthalate is subjected to an adsorption-crystallization step to provide high purity and high quality regenerated bis(2-hydroxyethyl) terephthalate.
[0089] For example, adsorption-crystallization may be carried out by adding the adsorbent using water as a solvent, filtering, and crystallizing.
[0090] Various solvents may be used for the adsorption-crystallization, but preferably a solvent capable of dissolving bis(2-hydroxyethyl) terephthalate is used as the solvent. As a specific example, in order to obtain the final reaction product, water is added as a solvent to the crude bis(2-hydroxyethyl) terephthalate dissolved by heating, and an adsorbent is added thereto, and then the solution obtained by filtration is subjected to cooling-crystallization and final filtration. As a result, a high-purity regenerated bis(2-hydroxyethyl) terephthalate can be obtained.
[0091] Water may be added in an amount of 100 to 500 parts by weight, specifically 200 to 400 parts by weight, and more specifically 300 to 350 parts by weight, relative to 100 parts by weight of crude bis(2-hydroxyethyl) terephthalate.
[0092] Furthermore, the dissolution temperature may be from 50°C to 95°C, specifically from 60°C to 85°C, and more specifically from 70°C to 75°C.
[0093] The added adsorbent can act to adsorb and remove other impurities. The adsorbent may be added in an amount of 0.1 to 3 parts by weight per 100 parts by weight of crude bis(2-hydroxyethyl) terephthalate. The type and form of the adsorbent are not particularly limited. For example, activated carbon may be used.
[0094] (Regenerated bis(2-hydroxyethyl) terephthalate) Bis(2-hydroxyethyl) terephthalate (BHET) obtained by depolymerization of waste polyester is called regenerated bis(2-hydroxyethyl) terephthalate (regenerated BHET, or r-BHET), but it should be understood as being different from the pure BHET compound.
[0095] Specifically, recycled BHET may contain by-products formed by side reactions with reagents or solvents used in various chemical steps during the depolymerization of waste polyester. These impurities may remain in trace amounts even after several purification steps. Thus, recycled BHET generally contains trace amounts of organic and inorganic impurities in addition to the main component BHET. For this reason, recycled BHET can also be considered as a kind of "composition" containing two or more components, i.e., "BHET composition."
[0096] Specifically, in addition to the main component BHET, the recycled BHET may contain trace amounts of heterogeneous organic components, such as BHET analogues, e.g., monohydroxyethyl terephthalic acid (MHET), BHET dimer, BHET trimer, by-products, e.g., diethylene glycol esters, inorganic metal ions, and residual solvent components.
[0097] However, the final recycled BHET obtained by the present invention is of high purity, contains less than certain levels of organic impurities, particularly diethylene glycol and by-products derived from diethylene glycol (such as DEG esters), or other oligomers and inorganic substances, and has excellent color quality.
[0098] This can be confirmed by analyzing the final product obtained by the above method by high performance liquid chromatography (HPLC) and calculating the relative ratio between the peak areas for each component. Specifically, the content of each component can be derived by measuring the peak area fraction (%) relative to the total peak area in the spectrum obtained using high performance liquid chromatography.
[0099] For example, the regenerated bis(2-hydroxyethyl) terephthalate produced by the above method may have a peak area fraction of bis(2-hydroxyethyl) terephthalate of 90% or more, 93% or more, or 95% or more, when measured by HPLC.
[0100] According to one embodiment, the regenerated bis(2-hydroxyethyl) terephthalate produced by the above method may have a peak area fraction of bis(2-hydroxyethyl) terephthalate of 96% or more when measured by HPLC. Specifically, the peak area fraction of bis(2-hydroxyethyl) terephthalate may be 96.5% or more, 97% or more, 97.5% or more, or 98% or more.
[0101] Furthermore, the recycled bis(2-hydroxyethyl) terephthalate produced by the above method may have a peak area fraction of organic impurities measured by HPLC of less than 5% in total, specifically less than 4%, less than 3%, less than 2%, less than 1%, or less than 0.7% in total.
[0102] According to one embodiment, the regenerated bis(2-hydroxyethyl) terephthalate produced by the above method may have a total peak area fraction of diethylene glycol ester compounds of less than 2% when measured by HPLC. Specifically, the total peak area fraction of diethylene glycol ester compounds may be less than 1.5%, less than 1%, less than 0.8%, or less than 0.7%.
[0103] The diethylene glycol ester compound may be, for example, a condensation product between an aromatic dicarboxylic acid, such as terephthalic acid, and diethylene glycol. As another example, the diethylene glycol ester compound may be a condensation product between an aromatic dicarboxylic acid, such as terephthalic acid, and a glycol (e.g., ethylene glycol) in addition to diethylene glycol. As a specific example, the diethylene glycol ester compound may include at least one of 2-hydroxyethyl [2-(2-hydroxyethoxy)ethyl] terephthalate and bis [2-(2-hydroxyethoxy)ethyl] benzene-1,4-dicarboxylate.
[0104] Furthermore, the regenerated bis(2-hydroxyethyl) terephthalate produced by the above method can have a total oligomer peak area fraction of 3% or less when measured by HPLC, which is a significantly superior level in terms of purity and quality compared with the range of 10-20% of oligomer substances present in the product obtained by depolymerization in the conventional method.
[0105] Specifically, the regenerated bis(2-hydroxyethyl)terephthalate produced by the above method may have a peak area fraction of BHET dimer of less than 3%, less than 2%, less than 1%, or less than 0.7% when measured by HPLC. Furthermore, the regenerated bis(2-hydroxyethyl)terephthalate produced by the above method may have a peak area fraction of BHET trimer of less than 1%, less than 0.5%, less than 0.3%, less than 0.1%, or 0% when measured by HPLC.
[0106] In addition, the final product may further contain impurities having a structure similar to that of bis(2-hydroxyethyl)terephthalate. For example, it may contain at least one selected from the group consisting of monohydroxyethyl terephthalate (MHET), bis(2-hydroxypropyl)terephthalate, and monohydroxyethylethoxyterephthalate. When measured by HPLC, the peak area fraction of the impurity having a structure similar to that of bis(2-hydroxyethyl)terephthalate may be less than 3%, less than 2%, less than 1%, or less than 0.5%.
[0107] Furthermore, the recycled bis(2-hydroxyethyl) terephthalate produced by the above method may have a yellowness index (YID) of 3.0 or less as measured by a spectrophotometer. Specifically, the yellowness index may be 2.5 or less, 2.0 or less, 1.5 or less, or 1.0 or less.
[0108] Furthermore, the recycled bis(2-hydroxyethyl) terephthalate produced by the above method may have a total inorganic matter content of less than 5 ppm as measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES). Specifically, the total inorganic matter content may be less than 3 ppm, less than 1 ppm, or nearly 0 ppm.
[0109] [Mode of the invention] The present invention will be described in more detail below with reference to embodiments. However, these examples are provided for illustrative purposes only and the present invention is not limited thereto.
[0110] Example 1 1,000 g of waste polyester resin crushed to a particle size of 4 mm or less, 2,000 g of ethylene glycol, and 3.5 g of anhydrous zinc acetate were placed in a stainless steel (SUS) first reactor. The temperature inside the reactor was raised to 180°C, and depolymerization (first glycolysis reaction) was carried out for 2 hours.
[0111] The resulting reaction product (first reaction product) was transferred to a second reactor and cooled to 150° C. 2,000 g of ethylene glycol was further added thereto, and depolymerization (second glycolysis reaction) was carried out for 2 hours while maintaining the reactor temperature at 150° C.
[0112] The resulting reaction product (second reaction product) was cooled to 120° C. by vacuum flashing, and 16 g of a filter aid (Celite (trademark) 545) was added thereto, followed by pressure filtration to perform solid-liquid separation.
[0113] The separated liquid reaction product was passed through a column packed with ion exchange resin (Bonlite BC107(H)) to remove ionic impurities, and a mixture containing bis(2-hydroxyethyl) terephthalate and ethylene glycol (third reaction product) was obtained.
[0114] This mixture (third reactant) was transferred to a 10-liter distillation apparatus and subjected to vacuum distillation at 130° C. to recover unreacted ethylene glycol.
[0115] The reaction product from which ethylene glycol had been removed (fourth reaction product) was thin-film evaporated in a thin-film evaporator (VKL70-4S manufactured by VTA) at 220°C and 0.08 Torr to obtain 1,040g of a product from which dimers and higher oligomers had been removed. Then, for adsorption-crystallization, 1,040g of the above product and 3,120g of distilled water were charged into a 20-liter glass reactor and dissolved at a temperature of 70°C, and then 5.2g of activated carbon was added thereto, followed by stirring for 30 minutes and filtration. The filtrate was cooled to room temperature for crystallization, filtered, and dried in a vacuum oven. As a result, 990g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained.
[0116] Example 2 980 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Example 1, except that the first glycolysis reaction was carried out at 180° C. for 1 hour.
[0117] Example 3 985 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Example 1, except that 1,000 g of waste fiber was used as the raw material for the waste polyester.
[0118] Example 4 A final product containing bis(2-hydroxyethyl) terephthalate (992 g) was obtained through the same procedure as in Example 1, except that 1,000 g of discarded banners were used as the raw material for the waste polyester.
[0119] Example 5 Through the same procedure as in Example 1, except that the adsorption-crystallization step was not performed after the thin-film evaporation, 1,050 g of the final product containing bis(2-hydroxyethyl) terephthalate was obtained.
[0120] Comparative Example 1 In a stainless steel (SUS) reactor, 1,000 g of waste polyester resin with a particle size of 4 mm or less, 4,000 g of ethylene glycol, and 3.5 g of anhydrous zinc acetate were charged. The temperature inside the reactor was raised to 196°C, and depolymerization (glycolysis reaction) was carried out for 4 hours. The resulting reaction product was cooled to 30°C, and crystallization of bis(2-hydroxyethyl) terephthalate was carried out for 2 hours. The resulting slurry of bis(2-hydroxyethyl) terephthalate and ethylene glycol was subjected to solid-liquid separation using a centrifuge. The bis(2-hydroxyethyl) terephthalate obtained by centrifugation was washed twice with a sufficient amount of distilled water, and the residual solvent was removed in an oven to obtain approximately 1,010 g of a final product containing bis(2-hydroxyethyl) terephthalate.
[0121] Comparative Example 2 Approximately 1,000 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Comparative Example 1, except that the glycolysis reaction was carried out at 210°C.
[0122] Comparative Example 3 The first glycolysis reaction was carried out at 196° C. for 4 hours, and approximately 1,020 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Example 1, except that neither the second glycolysis reaction nor the adsorption-crystallization was carried out.
[0123] Comparative Example 4 Approximately 730 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Example 1, except that the first glycolysis reaction was carried out at 150°C for 10 minutes and the second glycolysis reaction was carried out at 190°C for 1 hour and 30 minutes.
[0124] In such cases, this method was problematic because the first glycolysis reaction was carried out at a low temperature, which resulted in the filtration of a large amount of unreacted waste PET residue in the final reaction, which took more than 10 hours and reduced the final yield.
[0125] Comparative Example 5 Approximately 1,050 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Example 1, except that the first glycolysis reaction was carried out at 210°C and the second glycolysis reaction was carried out at 250°C.
[0126] Comparative Example 6 Approximately 995 g of a final product containing bis(2-hydroxyethyl) terephthalate was obtained through the same procedure as in Example 1, except that the unreacted glycol was recovered at 160°C.
[0127] (Test Example) The resulting products (recycled bis(2-hydroxyethyl) terephthalate) of the examples and comparative examples were tested as follows, and the results are summarized in Table 1 below.
[0128] (1) Composition - High Performance Liquid Chromatography (HPLC) About 0.01 g of the sample was diluted in about 20 ml of methanol and then measured by HPLC. Model:Waters e2695 Column: C18 (4.6 x 250 mm), 5 μm UV detector: 242 nm Injection volume: 10μl Eluent (gradient) A: H2O+H3PO4, B: acetonitrile
[0129] (2) Residual Solvents - Gas Chromatography (GC) About 0.1 g of the sample was diluted in about 10 ml of CHCl3, filtered through a 0.45 μm filter, and then measured by GC. Model: Agilent 7890B Column: DB-624 (30m x 0.25mm x 1.4μm) Oven temperature: 60℃(2min)-10℃ / min-200℃(0min)-20℃ / min-260℃(5min) Injection temperature: 250℃ Detector temperature: 250℃ Flow rate: 1.5ml / min (N2), split ratio: 1 / 50
[0130] (3) Melting point - Differential scanning calorimetry (DSC) Melting points (mp) were measured using a differential scanning calorimeter (DSC, TA Instruments Q20) by heating from 30° C. to 280° C. at a heating rate of 10° C. / min.
[0131] (4) Inorganic substances - inductively coupled plasma atomic emission spectrometry (ICP-AES) 0.3 g of sample was treated with ultrasound and diluted with ultrapure water. The content (ppm) of inorganic substances was measured using ICP-AES (Agilent model 5100) (detection limit 5 ppm).
[0132] (5) Yield The weight percentage of bis(2-hydroxyethyl) terephthalate actually obtained in the Examples and Comparative Examples was calculated based on the maximum weight of bis(2-hydroxyethyl) terephthalate obtained from 1,000 g of polyethylene terephthalate by glycolysis reaction.
[0133] (6) Yellow index (YID) The samples were dissolved in dimethylformamide (DMF) at a concentration of 25% by weight at room temperature (23°C) to prepare a solution. Transmission data for this solution was acquired using a Hunterlab Color Flex EZ with illuminant D65 at an observer angle of 2°. YID values were calculated using the color analyzer software.
[0134] [Table 1]
[0135] As can be seen from the above table, the products obtained in Examples 1 to 5 had a high BHET ratio, no inorganic impurities, low YID values, and the content of DEG-derived esters was minimized. The polyester resin polymerized with high purity from recycled BHET has excellent thermal properties such as glass transition temperature, melting point, and crystallization temperature, and therefore can reproduce the structural regularity, molecular weight, and excellent thermal properties of virgin polyester resin.
[0136] In contrast, the products obtained in Comparative Examples 1 and 5 had problems such as containing a large amount of dimer or DEG-derived ester, having poor color quality due to a high yellowness index (YID), or having a significantly low yield.
Claims
1. 1. A process for preparing regenerated bis(2-hydroxyethyl) terephthalate, comprising the steps of: (1) subjecting waste polyester to depolymerization by a first glycolysis reaction at a temperature of 180° C. to 200° C. to obtain a first reactant; (2) subjecting the first reactant to depolymerization by a second glycolysis reaction at a temperature of 150° C. to 170° C. to obtain a second reactant; (3) subjecting the second reactant to ion exchange with an ion exchange resin to obtain a third reactant; (4) removing unreacted glycol from the third reactant by distillation at a temperature of 150° C. or less to obtain a fourth reactant; (5) subjecting the fourth reactant to distillation to obtain crude bis(2-hydroxyethyl) terephthalate; A method comprising:
2. 2. The method for preparing recycled bis(2-hydroxyethyl) terephthalate according to claim 1, wherein the waste polyester has a particulate or fibrous form with a particle size of 4 mm or less.
3. 2. The method for preparing recycled bis(2-hydroxyethyl) terephthalate according to claim 1, wherein the first glycolysis reaction in step (1) is carried out in the presence of a catalyst, the catalyst comprising a metal acetate or an anhydride or hydride thereof, and is used in an amount of 0.2 parts by weight to 0.4 parts by weight based on 100 parts by weight of the waste polyester resin.
4. 2. The method for preparing regenerated bis(2-hydroxyethyl) terephthalate according to claim 1, further comprising the steps of cooling the second reactant to 120° C. or less and adding a filter aid to filter the second reactant prior to the ion exchange in step (3).
5. 2. The method for preparing regenerated bis(2-hydroxyethyl) terephthalate according to claim 1, further comprising the step of removing insoluble contaminants from the second reactant by filtration prior to the ion exchange in step (3).
6. The method for preparing recycled bis(2-hydroxyethyl) terephthalate according to claim 1, wherein the ion exchange resin in step (3) is used in an amount of 1 to 20 parts by weight based on 100 parts by weight of the waste polyester, and includes at least one selected from the group consisting of strong acid cation exchange resins, weak acid cation exchange resins, and chelating resins.
7. 2. The process for preparing regenerated bis(2-hydroxyethyl) terephthalate according to claim 1, wherein the distillation to remove unreacted glycol in step (4) is conducted at a temperature of from 100° C. to 130° C.
8. 2. The method for preparing regenerated bis(2-hydroxyethyl) terephthalate according to claim 1, wherein the distillation to obtain crude bis(2-hydroxyethyl) terephthalate is carried out by thin film evaporation under a pressure of 0.05 Torr to 0.4 Torr.
9. The method for preparing regenerated bis(2-hydroxyethyl) terephthalate according to claim 1, wherein the method further comprises a step of adsorption-crystallizing the crude bis(2-hydroxyethyl) terephthalate after the distillation in step (5), and the adsorption-crystallization is carried out by adding an adsorbent using water as a solvent, filtering, and crystallizing.
10. 2. The regenerated bis(2-hydroxyethyl) terephthalate prepared by the method according to claim 1, wherein the regenerated bis(2-hydroxyethyl) terephthalate has a peak area fraction of 96% or more in total and a peak area fraction of diethylene glycol (DEG) ester compounds of less than 2%, as measured by high performance liquid chromatography (HPLC).
11. The regenerated bis(2-hydroxyethyl) terephthalate according to claim 10, wherein the total peak area fraction of oligomers is 3% or less when measured by high performance liquid chromatography.
12. The recycled bis(2-hydroxyethyl) terephthalate of claim 10, having a yellowness index (YID) of 3.0 or less as measured by a spectrophotometer.
13. 11. The regenerated bis(2-hydroxyethyl) terephthalate of claim 10, having a total inorganic matter content of less than 5 ppm as measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES).